Hubungan Pengetahuan Kesehatan Gigi dan Mulut Terhadap Kualitas Hidup Lanjut Usia - Ahza, Laila; Budiman, Johan Arief; Asia, Rr. Asyurati (Puslitbang Sinergis Asa Professional, 2024)
According to Indonesia's Central Bureau of Statistics in 2021, the elderly population constituted 10.7% (29,128,542 individuals) of the total population in 2020. This proportion is projected to increase to 16.6% in 2035 and 19.9% in 2045. Knowledge of personal health significantly influences behavior, aligning with the level of understanding possessed. Oral health knowledge is a critical factor impacting dental and oral hygiene among the elderly. Poor oral health knowledge is commonly observed in older adults with lower socioeconomic status. The quality of life in the elderly is closely linked to oral health status. This study examined the relationship between oral health knowledge and quality of life among the elderly in Sembawa Subdistrict. It employed an observational analytic design with a cross-sectional approach. The sample consisted of elderly individuals aged 60–65 years, both male and female, visiting four elderly care centers (Posyandu Lansia) and the outpatient elderly clinic at UPTD Puskesmas Sembawa. Data were collected using a questionnaire adapted from oral health knowledge and the OHRQoL-13 quality-of-life questionnaires. Statistical analysis was conducted to assess relationships between variables, with significance set at p<0.05. Regression analysis of gender, age, and education characteristics showed no significant relationship with quality of life, with p-values of 0.948, 0.342, and 0.395, respectively (p>0.05). However, a significant positive relationship was found between oral health knowledge and quality of life, with an r-value of 0.168 and a significance level of 0.040 (p<0.05). In conclusion, while gender, age, and education were not statistically significant predictors of quality of life, oral health knowledge showed a positive and significant relationship with quality of life among the elderly.